Pengaruh Efektivitas Penyuluhan Perpajakan dan Kepatuhan Wajib Pajak terhadap Penerimaan Pajak: Studi pada Kantor Wilayah DJP Jawa Timur II - Mutia Taqina Gamat; Annas Rahmat Ramadhani; Putry H. Nadeak; Fransisca Maya Permatasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to evaluate the extent to which tax outreach activities and taxpayer compliance contribute to the increase in tax revenue. The research utilizes data from the Regional Office of the Directorate General of Taxes (DJP) East Java II, including records of outreach activities, taxpayer compliance, and tax revenue over a four-year period (2021–2024). A quantitative approach is employed, using linear regression analysis as a statistical tool to examine the relationships among the studied variables. The findings reveal that the effectiveness of tax outreach activities has a significant positive impact on increasing tax revenue, highlighting the strategic role of fiscal education in promoting taxpayer compliance and contributions. However, taxpayer compliance itself shows a negative contribution to tax revenue, suggesting the presence of other factors that may mediate or moderate this relationship. These results underscore that effective tax outreach can enhance tax awareness, ultimately leading to the optimization of tax revenue. Therefore, it is essential for the government to continuously improve the effectiveness of tax outreach programs to ensure the achievement of optimal tax revenue targets.